ANALYSIS OF INFLAMMATORY DISEASES OF THE UPPER RESPIRATORY TRACT AND ANTIBIOTIC DRUGS USED IN THEM - Yodgorova N.T., Mamanov J.B., Makhsudkhojayeva Kh.M. (Central Asian Journal of Medicine, 2025)
The purpose of the study: to identify cases of infection with inflammation of the upper respiratory tract and their sensitivity to antibiotics of the population of the Republic of Uzbekistan for the period 2023-2024 in administrative regions (by cross section of Regions). Materials and methods: in the bacteriological Lobaratorium of the Tashkent Medical Academy of the Republic of Uzbekistan, infections detected in patients with nasal infections from the second half of 2023 to the beginning of 2024, as well as microorganisms detected in them, their sensitivity to antibiotics were analyzed. Bacteriological, statistical methods were used. Results analysis and discussion. During this 6-month period, 148 patients (30 men, 118 women) had complaints of inflammatory diseases in the nasal cavity. Samples from them were collected in 145 of the total patients when the laboratory was diagnosed with 160 different bacteria (Streptococcus ssp.-25%, Staphylacocus aureus-30%, Candida ssp.-20%, Proteus mirabilis -10%, Pseudomonas auriginosa-10% and Klebsiella ssp.-5%). Microorganisms were not detected in 3 patients. Conclusion: as a result of the analyzes, we can see more (80%) women with inflammation of the nose get sick (the average age was 30-35). The bacterium that causes the most inflammation is Staphylacococcus aureus (30%), as well as the bacteria from the most effective antibiotics: sulfamethoxazole, Levofloxocin, amoxicillin and ampicillin, gave a good result.